Reappraisal of thienopyridine pretreatment in patients with non-ST elevation acute coronary syndrome: a systematic review and meta-analysis. (24th October 2014) - Bellemain-Appaix, Anne; Kerneis, Mathieu; O'Connor, Stephen A; Silvain, Johanne; Cucherat, Michel; Beygui, Farzin; Barthélémy, Olivier; Collet, Jean-Philippe; Jacq, Laurent; Bernasconi, François; Montalescot, Gilles
Abstract : Objective To investigate the effect of pretreatment with P2Y12 receptor inhibitors compared with no pretreatment on efficacy and safety of treatment of non-ST elevation acute coronary syndrome (ACS). Data sources Two reviewers independently searched Medline, Embase, Cochrane Controlled Trials, and BioMed Central databases for randomized placebo controlled trials and observational studies from August 2001 to March 2014. Study eligibility Studies must have reported both all-cause mortality (primary efficacy endpoint) and major bleeding (safety endpoint) outcomes. Data extraction Data on sample size, characteristics, drug dose and delay of administration, and outcomes were independently extracted and analyzed. Data synthesis A random-effect model was applied. The analysis was performed (i) in all patients independently of the management strategy and (ii) only in patients undergoing percutaneous coronary intervention. Results Of the 393 titles identified, seven (four randomized controlled trials, one observational analysis from a randomized controlled trial, and three observational studies) met the inclusion criteria. No study was identified for ticagrelor or cangrelor, and analyses were thus limited to thienopyridines. A total of 32 383 non-ST elevation ACS patients were included, 18 711 coming from randomized controlled trials. Of these, 55% underwent percutaneous coronary intervention (PCI). Pretreatment was not associated with a significant lower risk of mortality in all patients (odds ratio 0.90 (95% confidence interval 0.75 to 1.07), P=0.24), in particular when considering only the randomized controlled trials (odds ratio 0.90 (0.71 to 1.14), P=0.39). Similar results were observed in the cohort of patients undergoing PCI. A significant 30-45% excess of major bleeding was consistently observed in all patients (odds ratio 1.32 (1.16 to 1.49), P<0.0001) and in those undergoing PCI, as well as in the subset analyses of randomized controlled trials of these two cohorts of patients. There was a reduction in major adverse cardiovascular events in the analysis of all patients (odds ratio 0.84 (0.72 to 0.98), P=0.02), driven by the old clopidogrel studies (CURE and CREDO), but the difference was not significant for the cohort of patients undergoing PCI. Stent thrombosis, stroke, and urgent revascularization did not differ between groups (pretreatment v no pretreatment). The results were consistent for both thienopyridines and confirmed in sensitivity analyses. Limitations Analysis was not performed on individual patient's data. Conclusion In patients presenting with non-ST elevation ACS, pretreatment with thienopyridines is associated with no significant reduction of mortality but with a significant excess of major bleeding no matter the strategy adopted, invasive or not. Our results do not support a strategy of routine pretreatment in patients with non-ST elevation ACS.